Pembuatan Mikrokapsul Phycocyanin Menggunakan Maltodekstrin sebagai Bahan Pelapis dengan Metode Spray Drying - Muhammad Nasyarudin Iqbal; Hadiyanto Hady (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Microalgae have been considered aspotential source of nutritional value. Phycocyanin is one of high added value compound extracted from microalgae that can be used as pharmaceutical products, coloring agent and food nutrition enhancer. Therefore, the potential of phycocyanin need to be explored and developed for its use as an active ingredient in functional food. However, the application of phycocyanin as active compounds in functional foods is eventually accompanied by a stability issue since it is vulnerable to light, moisture content and temperature resulting in the degradation of proteins. Microencapsulation is an effective and economical method to maintain the stability of phycocyanin. One common method of microencapsulation isspray drying, while maltodextrin is the common coating material for spray drying. This study aims to describe the potential of spray drying for phycocyanin encapsulation process. Furthermore, the  characterization of microcapsules psychochemical properties, and evaluate the performance of the storage stability and release controls will be also described. This review discussesnumerous works about the microencapsulation of phycocyanin using maltodextrins as coating material and microencapsulation by spray dying method.